ADDIE Model Development (Analisys, Design, Development, Implemetation, Evaluation) - Torang Siregar Torang; Roiz Zulhadi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Agama Islam YAPTIP Chadijah Ismail Pasaman Barat, 2025)
The ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model is one of the systematic approaches that is widely used in the design and development of learning, especially in the context of modern education. The model consists of five main stages that are mutually continuous. The first stage, analysis, focuses on identifying the needs, problems, and characteristics of students to determine relevant learning objectives. The second stage, design, involves planning learning strategies, formulating goals, and selecting appropriate media or methods. Furthermore, the development stage is directed at the creation of learning products, including the development of teaching materials, media, and evaluation instruments. The implementation stage includes the implementation of the learning plan in the field or in the classroom, as well as monitoring the implementation process to ensure its effectiveness. Finally, the evaluation stage plays a role in measuring the effectiveness and efficiency of the learning program through formative and summative evaluations, in order to provide continuous improvement feedback. This journal comprehensively discusses each stage in the ADDIE model and provides examples of its application in various educational contexts, both online and face-to-face. With the support of references from various up-to-date sources, it is hoped that this article can provide comprehensive insights for educators, curriculum developers, and education practitioners in designing more effective, efficient, and adaptive learning. In addition, the journal also emphasizes the importance of the evaluation cycle in the ADDIE model as the main foundation in the development of instructional needs based on the needs of learners.